Magnetic Resonance Imaging of the Small Bowel in Crohn’s Disease: A Systematic Review and Meta-Analysis - Osman Ahmed; David Mario Rodrigues; Geoffrey C. Nguyen (Canadian Journal of Gastroenterology and Hepatology)
Introduction. Crohn’s disease is most commonly found in the terminal ileum and colonic region. Magnetic resonance has become a useful modality for assessing small bowel activity. In this study, we performed a systematic review and meta-analysis on the use of MR in detecting small bowel activity as well as extramural complications in Crohn’s patients. Methods. Two independent reviewers sorted through articles until October 2, 2014. We included both studies providing raw data for pooling and studies without raw data. Sensitivity, specificity, likelihood ratios, and 95% confidence intervals were calculated for each study. Results. There were 27 included studies, of which 19 were included in the pooled analysis. Pooled analysis of the 19 studies (1020 patients) with raw data revealed a sensitivity of 0.88 (95% CI 0.86 to 0.91) and specificity was 0.88 (95% CI 0.84 to 0.91). In regard to detecting stenosis, pooled sensitivity was 0.65 (95% CI 0.53 to 0.76) and specificity was 0.93 (95% CI 0.89 to 0.96). Conclusion. MR imaging provides a reliable alternative in detecting small bowel activity in patients with Crohn’s disease. Its advantages include high diagnostic accuracy and no radiation exposure while its disadvantages include high cost and limited availability.